Housing for the elderly : evaluation of the effectiveness of congregate residences - 258259 Malozemoff, Irene K.; Anderson, John G.; Rosenbaum, Lidia V. (Boulder, Colo. : Westview Press, 1978)
Bibliography: p. 310-320.